Association of adverse childhood experiences with subjective cognitive decline in adulthood: Findings from a population-based study. (28th October 2022) - Baiden, Philip; Cassidy, Jessica; Panisch, Lisa S.; LaBrenz, Catherine A.; Onyeaka, Henry K.
Abstract: Objective: Adverse childhood experiences have been found to be associated with negative outcomes during adulthood. Emerging research indicates that adverse childhood experiences may elevate the risk for Alzheimer's disease. Yet, few studies have investigated the association between adverse childhood experiences and subjective cognitive decline among middle-aged and older adults in the United States. The objective of this study was to investigate the association between adverse childhood experiences and subjective cognitive decline among middle-aged and older adults in the United States. Methods: Data for this study were obtained from the 2019 Behavioral Risk Factor Surveillance Survey. An analytic sample of 50, 277 adults aged 45 to 79 years (53.3% female) from 15 states was analyzed using binary logistic regression. The outcome variable investigated in this study was subjective cognitive decline, and the main explanatory variable was adverse childhood experiences. Results: Of the 50, 277 respondents, 10.3% reported experiencing subjective cognitive decline during the past year, and 14.5% had four or more adverse childhood experiences. We found a dose-response association between adverse childhood experiences and subjective cognitive decline. Respondents who had four or more adverse childhood experiences had 2.98 times higher odds of having subjective cognitive decline when compared to respondents with no adverse childhood experiences (aOR = 2.98, 95% CI = 2.56-3.48). Other factors associated with subjective cognitive decline have been identified and discussed. Conclusion: The findings of this study provide evidence indicating that early life factors may be linked with cognitive decline in later adulthood. The findings of this study are discussed with implications for practice and research.